The genetic correlation and causal association between key factors that influence vascular calcification and cardiovascular disease incidence - Ni, Xiaolin; Liu, Lei; Yao, Yao; Zhang, Chi; Su, Huabin; Lv, Yuan; Li, Rongqiao; Sun, Liang; Zhou, Qi; Zhu, Xiaoquan; Yang, Ze; Chen, Zuoguan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Serum calcium, vitamin D, and vitamin K levels are key determinants of vascular calcification, which itself impacts cardiovascular disease (CVD) risk. The specific relationships between the levels of these different compounds and particular forms of CVD, however, remain to be fully defined. Objective: This study was designed to explore the associations between these serum levels and CVDs with the goal of identifying natural interventions capable of controlling vascular calcification and thereby protecting against CVD pathogenesis, extending the healthy lifespan of at-risk individuals. Methods: Linkage disequilibrium score (LDSC) regression and a two-sample Mendelian randomization (MR) framework were leveraged to systematically examine the causal interplay between these serum levels and nine forms of CVD, as well as longevity through the use of large publically accessible GWAS datasets. The optimal concentrations of serum Ca and vitamin D to lower CVD risk were examined through a restrictive cubic spline (RCS) approach. Results: After Bonferroni correction, the positive genetic correlations were observed between serum Ca levels and myocardial infarction (MI) (p =1.356E-04), as well as coronary artery disease (CAD) (p =3.601E-04). Negative genetic correlations were detected between levels of vitamin D and CAD (p =0.035), while elevated vitamin K1 concentrations were causally associated with heart failure (HF) (OR per 1-SD increase: 1.044), large artery stroke (LAS) (OR per 1-SD increase: 1.172), and all stroke (AS) (OR per 1-SD increase: 1.041). Higher serum Ca concentrations (OR per 1-SD increase: 0.865) and vitamin D levels (OR per 1-SD increase: 0.777) were causally associated with reduced odds of longevity. These findings remained consistent in sensitivity analyses, and serum Ca and vitamin D concentrations of 2.376 mmol/L and 46.8 nmol/L, respectively, were associated with a lower CVD risk (p<0.001). Conclusions: Our findings support a genetic correlation between serum Ca and vitamin D and CVD risk, and a causal relationship between vitamin K1 levels and CVD risk. The optimal serum Ca (2.376 mmol/L) and vitamin D levels (46.8 nmol/L) can reduce cardiovascular risk.